IMPROVING THE SPEAKING SKILL OF GRADE EIGHT STUDENTS AT MTS TAHFIZH AL MADINAH MALANG THROUGH PICTURE SERIES - Rizki Trisdianti (Graduate Program, University of Islam Malang, 2021)
ABSTRACTTrisdianti, Rizki. 2020. Improving the Speaking Skill Of Grade Eight Students at MTS TahfizhAl Madinah Malang Through Picture Series. Thesis, English Education Department, Postgraduate Program, Islamic University of Malang, Advisor: (1) Siti Rohani, S.Pd., M.Pd., Ph.D. Key Words: Speaking abilty, Recount Text, Picture Series. Speaking is one of the important skills for the students, because it plays an important role in communication. It is a complex skill which needs the understanding and mastering of language components such as pronunciation, grammar (structure), and vocabulary. Teaching speaking in English is very complicated. Many Junior High School students have problems in speaking. In the preliminary study conducted at MTS Tahfizh Al Madinah Malang, the researcher found that the students’ speaking ability was low. The students average score in speaking ability was 68, but the passing grade was 75. Most students tended to be passive to use English either in asking some questions to the teacher or in answering the questions given by the teacher. This condition inspired the writer to find out the constructive solution of this low achievement problem. The writer believes that this condition might be influenced by the techniques used by the teacher that cannot arouse the students’ interest and motivation. Concerning to the problem above, the writer conducted a classroom action research to the eight level students of Mts Tahfizh Al Madinah Malang by using picture series in teaching speaking. This study employed Collaborative Classroom Action Research design in which the researcher together with the classroom teacher planned the action. Implemented the action, observed the action, and made the reflection of the action, implemented the action, observed the action, and made the reflection of the action. This classroom action research consisted of two cycles, in which each cycle covered four main stages including: the planning of the action, the implementation of the action, classroom observation, and reflection. The primary data were taken from the results of speaking test. Meanwhile, the supporting data were gathered from interview and documentation. The result of the average score of the speaking test in the first cycle was M=71. This result did not achieve the target average score in this research that was M>75. Besides, the percentage of the students that reached the target score was 63% below the targeted percentage 85%. Therefore, the action were proceeded to the second cycle by revising the first action cycle by giving key words under the pictures. The result of the average score of the speaking test in the second cycle was better, M=77. Besides, the percentage of the students’ speaking skill that got the target score was 88%. It means that the result of the students’ speaking test improved in the second cycle and fulfilled the target of this research. Based on the results, it could be concluded that the use of picture series could improve the 8th year students’ speaking skill at Mts Tahfizh Al Madinah Malang two cycles. Then it is suggested to the English teachers to apply picture series as alternative media in teaching English, especially in teaching of recount text.